Anthropocentrism and Two Phenomenological Approaches to Animal Life - Mintautas Gutauskas (Problemos)
This article analyzes two phenomenological approaches to animal life in the context of criticism of anthropocentrism. The first part considers the question of anthropocentrism. Beginning with the posthumanist criticism of anthropocentrism as an ideology of human exceptionalism, the article proposes to reflect human anthropocentricity phenomenologically as a condition of experience. The second part discusses San Martín and Pintos’ approach, which, grounded in Husserl’s analysis of transcendental ego, considers the human-animal relation in terms of egotic subjectivity, corporeality, and the constitution of sense. San Martín and Pintos’ position is very important in the criticism of anthropocentrism, and yet it is considered insufficient when reflecting the diversity of human-animal relations. The third part analyses Depraz’s four-stage structure of empathy and aims to determine the conditions and limits of access to animals as liminal subjects. Corporeality is considered as the most general layer; the accessibility of animal consciousness, the approach to their experience, the possibilities and limits of it are analyzed. Finally, it is concluded that the two positions can contribute to the understanding of the limits of anthropocentrism and its failures.